A NEW SUBSPECIES OF SENECIO MOHAVENSIS (COMPOSITAE) REVEALS OLD–NEW WORLD SPECIES DISJUNCTION - COLEMAN, M.; FORBES, D. G.; ABBOTT, R. J. (Edinburgh Journal of Botany, 2001)
Examination of morphology, ploidy and interfertility in the two subspecies of the Old World Senecio flavus (Decne.) Sch. Bip. (Compositae) and the closely related New World S. mohavensis A. Gray does not support the subspecific taxonomy of S. flavus. On the basis of our results S. flavus subsp. breviflorus Kadereit is transferred to S. mohavensis as a new subspecies: S. mohavensis subsp. breviflorus (Kadereit) M. Coleman comb. nov. The new subspecies has a distribution that includes Arabia, the Middle East, Sinai, Iran, Afghanistan, Djibouti, and the Thar Desert of Pakistan. The type subspecies of S. mohavensis occurs in the Mojave and Sonoran deserts of North America, providing an unusual disjunct distribution at the species level. Separation from S. flavus is based upon differences in morphology and chromosome number. Senecio flavus is diploid (2n = 20), while both subspecies of S. mohavensis are tetraploid (2n = 40). Further support for the new taxonomic treatment is provided by the results of controlled crosses. No artificial hybrids have been generated from crosses made between the previously recognized subspecies of S. flavus, while crosses between the newly recognized subspecies of S. mohavensis have produced fertile hybrids. The fertility of the hybrids is significantly lower than the parental taxa (P<0.001), indicating partial genetic divergence since isolation. Previous studies of isozyme and cpDNA variation in all three taxa also support the new treatment. The similarity of the S. mohavensis subspecies suggests a relatively recent separation, although the amount of genetic divergence does not support a post-Colombian introduction. Given that land bridges to North America via Beringia and the North Atlantic last existed in the Oligocene, long-distance dispersal seems the most likely explanation. Natural dispersal to rather than from the New World is supported, but whether this took place in an easterly or westerly direction is unclear. The evolution of S. mohavensis remains equivocal.